Effects of mycorrhizal and Trichoderma treatment on enhancing maize tolerance to salinity and drought stress, through metabolic and enzymatic evaluation - Fatemeh Eftekhari; Mehdi Sarcheshmehpour; Azadeh Lohrasbi-Nejad; Naser Boroomand (BMC Plant Biology)
Abstract Background Nowadays, climate change has intensified environmental stresses, including salinity and drought stress. Salinity and drought significantly impair crop growth and yield by affecting physiological and biochemical processes. One of the ways to enhance environmental stress tolerance in plants is to improve their symbiotic relationships with soil microorganisms. This study investigates the impact of arbuscular mycorrhizal fungi (AMF) and Trichoderma harzianum (accession number: PV544806) inoculation on maize to trace the activated pathways under stress conditions. Maize plants were exposed to different stress conditions: salinity (S1D0), drought (S0D1), and a combination of both salinity and drought (S1D1). They received treatments with arbuscular mycorrhizal fungi (AMF) (M1T0), Trichoderma (M0T1), and a combination of both (M1T1). Results Inoculation of maize plants with AMF and T. harzianum markedly enhanced root dry weight, root volume, and total biomass under stress conditions. Additionally, the simultaneous inoculation of AMF and T. harzianum under combined salinity and drought conditions significantly affected traits such as dry weight of aerial parts, total biomass, and root colonization percentage compared to the non-inoculated control. Physiologically, the results also indicated that the inoculation significantly increased the activity of antioxidant enzymes SOD and APX. Results from GC-MS analysis and metabolic pathway analysis showed that the combined inoculation of AMF and Trichoderma in maize plants stimulated the production of specific secondary metabolites such as oxaloacetate, Δ1-piperidine-6-carboxylate, and cadaverine under stress conditions. Conclusions Based on this study’s findings, the use of AMF and T. harzianum can enhance maize growth and performance under salinity and drought stress by stimulating the production of secondary metabolites.